Insulin Signaling, the CNS, and Longevity - Canavan, Neil (MD Conference Express, 2008)
Numerous recent studies of animal models suggest a highly active role for the central nervous system in energy homeostasis. While this is not surprising, an expansion of these findings indicates that insulin signaling has a pronounced influence on the lifespan of a wide array of organisms.